The model of hybrid influence in the information sphere - Khryapynskyi , Anton (Pressing Problems of Public Administration, 2024)
An analysis of the specifics of the functioning and essence of the model of hybrid influence in the information sphere was carried out, as a result of which it was established that with the growing threat of cyber-attacks by national states, hackers and criminal organizations, it began to affect the way the world sees the Internet. Inadequate management of cyber threats puts users at risk, undermines trust in the Internet, and jeopardizes its ability to drive economic and social innovation. But at the same time, a misinformed and disproportionate response by authorities can potentially threaten Internet freedom and create an atmosphere of fear, uncertainty and doubt. Therefore, the future of the Internet and its continued growth will be determined by how governments and private organizations collectively respond to the scope and scale of cyberattacks.As governments feel pressure to mitigate the effects of cyberattacks, there is a growing risk that online freedoms and global connectivity will be severely curtailed in favor of national security. To avoid this, new models of incentives, accountability, and responsibility are urgently needed to increase cybersecurity readiness, reduce vulnerabilities, and ensure end-user security. The complexity and scale of cyber-attacks require a multi-stakeholder and expert-led response to keep the digital economy thriving and to restore confidence in internet security. Neither the public nor the private sector can handle the scope and scale of cyber threats alone. Because of the interconnected nature of the Internet, actions taken by individual stakeholders will do little to mitigate or eliminate cyber threats. Usually, the state reacts to new cyber threats, guided by the need to “do something” in the face of increasingly sophisticated cyber-attacks. However, such reactive responses will not effectively mitigate the threat and will lead to over-regulation. Effective action and network resilience to cyber threats can only come about through information sharing, strategic thinking and collaborative efforts by all stakeholders.It is argued that how stakeholders adapt to future cyberattacks could transform the Internet from a platform of openness and collaboration to a fragmented, closed, and insecure network environment. A fundamental change in the architecture and basic principles of the Internet could create a dystopian future of a protected walled garden, filtering access without encryption, anonymity, or privacy. The national security of nation-states will eclipse the freedoms and rights we now take for granted, creating a battle between perceived national security interests and end-user security measures. This can be avoided if the long-discussed need for a global cyber security culture takes on new relevance and urgency as cyber security becomes everyone’s responsibility. At the same time, cyber governance can no longer remain solely in the hands of the authorities, as the risk of being subjected to cyber-attacks is constantly increasing. Much of the global Internet infrastructure today is developed, owned and maintained by private actors, and due to the complexity and scale of cyber-attacks, governments alone are unable to provide inclusive and expert-led regulatory responses, and therefore private actors need to be encouraged to join discussions about the future of the Internet.